PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA DEPARTEMEN JARINGAN PT PLN ( PERSERO) AREA SURABAYA UTARA - NOVRI SETIAWAN, INDRA (Jurnal Ilmu Manajemen (JIM), 2013)
The safety and the working health of employee is one of the determination factors of Success Company, both the field production of goods and service. The employees are important asset of company. Therefore, how company attention to safety and working health employees interested to be researched. And the objective of this research is to know how the influence of safety and working health to employee’s productivity. The population in this research is employee Chain Service Department in PT PLN (Persero) APJ North Surabaya. Samples taken by 72 respondents with a saturated sample technique. The results of research showed that the safety, health in the workplace and employee’s productivity top rated by Chain Service Department in PT PLN (Persero) APJ North Surabaya. working safety and working health have strong influence on employee’s productivity Chain Service Department in PT PLN (Persero) APJ North Surabaya. Keywords: Safety, health , employee’s productivity.